Application of Predictive Maintenance in Hospital Heating, Ventilation and Air Conditioning Facilities - Gonzalo Sánchez-Barroso; Justo García Sanz-Calcedo (Emerging Science Journal, 2019)
The variety of a hospital’s users leads to different levels of requirements relating to indoor environmental conditions. The responsibility for generating these favourable conditions for the pathologies treated in the different areas of a hospital lies with heating, ventilating and air-conditioning (HVAC) system. They carry out the control of nosocomial infections. Consequently, establishing adequate maintenance plans for these facilities will have a high positive impact on economic and environmental management, on the one hand, and on people's health, on the other. The aim of this work is to analyse foreseeable information and results generated after applying condition-based maintenance (CBM) techniques. The Weibull distribution was used to model the distribution of equipment failures and the potential of the information obtained from applying the CBM methodology was highlighted. The results of this work represent an improvement in the working practise of the HVAC facilities hospital maintenance departments. They dispose of information to decide on investment in equipment taking into account maintenance costs. In addition, this allow analyse data to know current status of a piece of equipment or unit, thus establishing an optimized maintenance plan considering asset’s remaining useful life and associated maintenance costs.